Respuesta :
Answer:
The system of equations as described:
y = (-3/4)x + 3
y = -12
Combining two equations, we have:
=> -12 = (-3/4)x + 3
=> -15 = (-3/4)x
=> x = -15 x (-4/3) = 20
=> Solution is (20, -12)
=> Option A is correct.
Hope this helps!
:)
Step By Step:
The equations given to us are:
y = (-3/4)x + 3
y = -12
Now that we have y we can change that to -12
-12 = (-3/4)x + 3
-15 = (-3/4)x
x = -15 x (-4/3) = 20
This would give us (20, -12)
Answer
A. (20,-12)
Hope this helps
give brainliest if you please